2005
DOI: 10.1007/s10194-005-0216-8
|View full text |Cite
|
Sign up to set email alerts
|

A CARE pathway in medication–overuse headache: the experience of the Headache Centre in Pavia

Abstract: Medication-overuse headache (MOH) [1] is one of the headache forms that most frequently prompts patients to consult a specialist headache centre. Literature data indicate an approximately 1%-2% prevalence of MOH in the general population [2][3][4]. Around 40% of patients seen at headache centres present with a chronic form of headache and 80% of these chronic headache patients make excessive use of symptomatic drugs [4]. A 2003 study by Dowson on the profile of patients seen at UK headache centres revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…As in our previous study [13] 11% of the MOH patients failed to adhere to the follow-up program, in most cases because they were dissatisfied with a treatment approach based solely on advice to withdraw symptomatic drugs. This is a relatively high drop-out rate compared with other studies [15]. In the 2006 study, we showed that the rate of adherence to treatment is independent of the detoxification strategy proposed.…”
Section: Discussionmentioning
confidence: 62%
“…As in our previous study [13] 11% of the MOH patients failed to adhere to the follow-up program, in most cases because they were dissatisfied with a treatment approach based solely on advice to withdraw symptomatic drugs. This is a relatively high drop-out rate compared with other studies [15]. In the 2006 study, we showed that the rate of adherence to treatment is independent of the detoxification strategy proposed.…”
Section: Discussionmentioning
confidence: 62%
“…We found 27 studies (45 articles) reporting the treatment response to early discontinuation therapy (9,12,14,24,25,. Among them, 19 studies (37 articles) reported the results of Early discontinuation with preventive medication (9,12,24,25,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63)(64)(65)(66)(67)(68)(69).…”
Section: Resultsmentioning
confidence: 99%
“…We evaluated, in a prospective, non-randomized way, consecutive patients seen for the first time at the centre between May 2004 and January 2006 and who fulfilled revised ICHD-II criteria (7) for probable MOH (p-MOH). After giving their verbal informed consent to participate, patients were enrolled in the CARE I protocol (21). This consisted of a 2-month observational period during which the patients, awaiting hospitalization, monitored characteristics of headache and drug intake by means of an ad hoc diary (22).…”
Section: Methodsmentioning
confidence: 99%